A double-tracer technique to characterize absorption, distribution, metabolism and excretion (ADME) of [14C]-basimglurant and absolute bioavailability after oral administration and concomitant intravenous microdose administration of [13C6]-labeled basimglurant in humans. (1st February 2017) - Guerini, Elena; Schadt, Simone; Greig, Gerard; Haas, Ruth; Husser, Christophe; Zell, Manfred; Funk, Christoph; Hartung, Thomas; Gloge, Andreas; Mallalieu, Navita L.
Abstract: 1. The emerging technique of employing intravenous microdose administration of an isotope tracer concomitantly with an [ 14 C]-labeled oral dose was used to characterize the disposition and absolute bioavailability of a novel metabotropic glutamate 5 (mGlu5) receptor antagonist under clinical development for major depressive disorder (MDD). 2. Six healthy volunteers received a single 1 mg [ 12 C/ 14 C]-basimglurant (2.22 MBq) oral dose and a concomitant i.v. tracer dose of 100 μg of [ 13 C6 ]-basimglurant. Concentrations of [ 12 C]-basimglurant and the stable isotope [ 13 C6 ]-basimglurant were determined in plasma by a specific LC/MS-MS method. Total [ 14 C] radioactivity was determined in whole blood, plasma, urine and feces by liquid scintillation counting. Metabolic profiling was conducted in plasma, urine, blood cell pellet and feces samples. 3. The mean absolute bioavailability after oral administration (F) of basimglurant was ∼67% (range 45.7–77.7%). The major route of [ 14 C]-radioactivity excretion, primarily in form of metabolites, was in urine (mean recovery 73.4%), with the remainder excreted in feces (mean recovery 26.5%). The median tmax for [ 12 C]-basimglurant after the oral administration was 0.71 h (range 0.58–1.00) and the mean terminal half-life was 77.2 ± 38.5 h. Terminal half-life for the [ 14 C]-basimglurant was 178 h indicating presence of metabolites with a longer terminal half-life. Five metabolites were identified with M1-Glucuronide as major and the others in trace amounts. There was minimal binding of drug to RBCs. IV pharmacokinetics was characterized with a mean ± SD CL of 11.8 ± 7.4 mL/h and a Vss of 677 ± 229 L. 4. The double-tracer technique used in this study allowed to simultaneously characterize the absolute bioavailability and disposition characteristics of the new oral molecular entity in a single study.